Picture and Picture to Improve Descriptive Writing Skills in Class IV of Pretek 01 Elementary School - Timbul Prabowo (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve teacher skills, increase student activity, and improve student description writing skills with the Picture and Picture strategy.This classroom action research was conducted in two cycles with the research subjects of class IV SD Pretek 01, totaling 28 students. The research data were in the form of quantitative data and qualitative data which were analyzed using descriptive analysis techniques. The variables of this study were (1) teacher skills, (2) student activities and (3) learning outcomes. From the research results, it can be seen that the teacher's skills in cycle 1 got a score of 90 and in cycle 2 got a score of 92. Student activity increased from cycle I 70.24 and cycle II 76.08 there was an increase. Student learning outcomes also increased. From 28 students who scored ≥ 75 there were 13 students (45%) in cycle II experienced an increase. ≥ 75 there are 21 students (75%)